2014
DOI: 10.1039/c4sm01177e
|View full text |Cite
|
Sign up to set email alerts
|

Reentrance in an active glass mixture

Abstract: Active matter, whose motion is driven, and glasses, whose dynamics are arrested, seem to lie at opposite ends of the spectrum in nonequilibrium systems. In spite of this, both classes of systems exhibit a multitude of stable states that are dynamically isolated from one another. While this defining characteristic is held in common, its origin is different in each case: for active systems, the irreversible driving forces can produce dynamically frozen states, while glassy systems vitrify when they get kinetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
9
1
Order By: Relevance
“…During the last decade, numerous synthetic active systems have also become available [80], spurring the development of theoretical approaches to describe the emergent behavior in these non-equilibrium materials. In particular, it was found that dense active matter can also exhibit properties of supercooled liquids and vitrifying colloidal suspensions [6,8,11,[81][82][83][84][85][86][87][88][89][90], including slow structural relaxation, dynamic heterogeneity, varying degrees of fragility, and the ultimate formation of a kinetically arrested, amorphous solid state.…”
Section: Mode-coupling Theories For Active Mattermentioning
confidence: 99%
“…During the last decade, numerous synthetic active systems have also become available [80], spurring the development of theoretical approaches to describe the emergent behavior in these non-equilibrium materials. In particular, it was found that dense active matter can also exhibit properties of supercooled liquids and vitrifying colloidal suspensions [6,8,11,[81][82][83][84][85][86][87][88][89][90], including slow structural relaxation, dynamic heterogeneity, varying degrees of fragility, and the ultimate formation of a kinetically arrested, amorphous solid state.…”
Section: Mode-coupling Theories For Active Mattermentioning
confidence: 99%
“…Nonequilibrium glass transitions have recently emerged as a new type of dynamic arrest occurring in particle systems driven out of equilibrium by active forces [1,2]. The initial theoretical interpretation, based on the analysis of simple glass models driven by active forces [3], has been confirmed in several computer simulations of more realistic active matter models [1,[4][5][6][7][8][9][10][11][12][13][14]49]. A number of alternative theoretical approaches have now been proposed to describe this phenomenon [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of living active matter are found on all length scales, from microscopic motile bacteria to macroscopic flocks of birds, and also numerous synthetic active materials have recently become available [5]. The spatiotemporal dynamics exhibited by such systems range from swarming and giant number fluctuations [6, 7] to low-Reynolds-number turbulence [8][9][10][11] and motility-induced phase separation [12][13][14][15], illustrating the rich collective behavior that emerges from the nonequilibrium energy dissipation and active self-motility at the single-particle level.It was recently found that sufficiently dense assemblies of active matter can also exhibit hallmarks of glassy dynamics [16][17][18][19][20][21][22][23][24][25][26][27][28], including slow relaxation, dynamic heterogeneity, and ultimate kinetic arrest-akin to the behavior observed in non-active supercooled liquids and dense colloidal suspensions [29]. For passive systems, the process of glass formation has been widely studied over the last few decades, resulting in multiple compelling theoretical scenarios for the conventional glass transition [29][30][31].…”
mentioning
confidence: 99%